Can the preoperative value of VLPP and MUCP predict the postoperative quality of life? - Drahorádová, Petra; Mašata, Jaromír; Martan, Alois; Švabík, Kamil; Pavlíková, Markéta (Prague Medical Report, 2009)
The aim of this study was to determine whether low values of VLPP (Valsava Leak Point Pressure) and low values of MUCP (Maximal Urethral Closure Pressure) before operation can predict quality of life (QOL) after anti-incontinence surgery. METHODS: 72 stress incontinent women were included in this study. All women underwent anti-incontinent surgery. We compared the quality of life using I-QOL (Incontinence Quality of Life) assessment with parameters of urodynamic measurement VLPP and MUCP The women filled in an I-QOL questionnaire before surgery and three month afterwards. RESULTS: As in other studies, low preoperative value of the VLPP < or =60 cmH2O was not related to a statistically lower quality of life (average I-QOL for VLPP < or =60 cmH2O was 38.4 and 48.9 for VLPP > 60 cmH2O). We did not find statistically significant lower quality of life in women with MUCP < or =20 cmH2O (average I-QOL 38.2, and for MUCP > 20 39.7). The quality of life was significantly changed after successful anti-incontinent operation, but independently of the preoperative value of VLPP or MUCP, average I-QOL for VLPP < or =60 cmH2O was 81.5 and 82.8 for VLPP > 60 cmH20, for MUCP < or =20 cmH2O 79.5, and 86.4 for MUCP >20. CONCLUSIONS: Low preoperative values of MUCP and VLPP did not correlate with QOL. Preoperative VLPP and MUCP do not predict the QOL after anti-incontinent surgery.
Keywords: financování organizované; stresová inkontinence moči; Female; Quality of Life; ženské pohlaví; urodynamika; Urodynamics; Urinary Incontinence, Stress; kvalita života; Urethra; lidé; uretra; Valsalva Maneuver; Financing, Organized; Urogenital Surgical Procedures; urogenitální chirurgické výkony; Valsalvův manévr; lidé středního věku; Middle Aged; Humans